Pengaruh Budaya Kerja dan Evaluasi Kerja terhadap Prestasi Kerja Karyawan PT Larasindo Duta Persada Medan - Charin Charin; Syawaluddin Syawaluddin; Mila Asmawiani Okta; Thomas Sumarson Goh (Universitas Batanghari Jambi, 2023)
Employee performance is very important in the company to achieve its goals, so various efforts are made to improve it. Employee performance is influenced by many factors such as work culture and employee job evaluation. The purpose of this study was to determine the effect of work culture and work evaluation on employee performance at PT Larasindo Duta Persada Medan. The research method used is a survey approach analysis method, the type of research is quantitative descriptive, the research method is carried out by questionnaires, interviews, and documentation studies. The analytical method used is multiple linear regression. The population is employees of PT Larasindo Duta Persada Medan. The sample in the study to be tested is 45 people. The data analysis technique used is the reliability validity test, the classical assumption test, the coefficient of determination (R2) test, multiple regression analysis, and hypothesis testing. The results of this study indicate that simultaneously work culture and work evaluation affect the work performance of PT Larasindo Duta Persada Medan employees. The work culture variable partially has no effect on work performance, while the partial job evaluation has a significant effect on work performance. work culture and work evaluation explain its effect on employee performance at PT Larasindo Duta Persada Medan with a coefficient of determination of 0.230 which means that 23% of work performance variables can be explained by work culture and work evaluation variables and the remaining 77% is varied by other factors that are not researched such as organizational culture, job satisfaction and others